Mobile UiTM programmes qualification checking system using Analytical Hierarchy Process (AHP) technique / Nur Fadhlina Ab Rahman - Ab Rahman, Nur Fadhlina (2015)
Mobile Computing is an umbrella term used to describe technologies that enable people to access network services anyplace, anytime or anywhere and involves mobile software. Mobile software deals with the characteristics and requirements of mobile applications. A mobile applications is a computer program designed to run on smartphones, tablet computers and other mobile devices and can be use either offline or online. Mobile applications are created to access “Selangkah ke UiTM” application, user will have the capacity to get to the system effortlessly. Analytic Hierarchical Process (AHP) is unitary of the extensively used multi-criteria decision making (MCDM) methods. AHP is a trendy technique that helps to make selection based on decision offered. m-Selangkah helps SPM leavers to access all the applications quickly and easily by download the applications. This application had been made by using the Analytic Hierarchy Process (AHP) technique which is one of the techniques that can help SPM leavers to make selection on the best programmes. The process in decision making is integrated with AHP technique. The application could gain from the AHP approach and could be applied for the user because of its ease of implementation. This application will help the SPM leavers by providing a few criteria for them and from the criteria the applications will navigate them to choose the best programmes for them. In order to complete the research and development of this project, M-Selangkah is developed based on phases in the RAD Model which are Preliminary Study, System Analysis, System Design, System Development, System Testing and Evaluation and Documentation. The functionality of m-Selangkah application has been tested using real data. The usability of this application evaluated by conduct a set of questionnaire to the random respondents. The feedback received from the respondent is positive. This application is potential to introduce to the SPM leavers. For the future work, m-Selangkah application can be upgrade to overcome the limitations. It also can enhance to be more functionality at client-side to make this application more benefit for the SPM leavers at the future.